Evaluation of prenatal diabetes mellitus and other risk factors for craniofacial microsomia. Issue 11 (30th March 2019) - Siebold, Babette; Heike, Carrie L.; Leroux, Brian G.; Speltz, Matthew L.; Drake, Amelia F.; Johns, Alexis L.; Kapp‐Simon, Kathleen A.; Magee, Leanne; Luquetti, Daniela V.
Abstract : Objectives: Craniofacial microsomia (CFM) is a congenital condition that typically involves hypoplasia of the ear and jaw. It is often associated with adverse effects such as hearing loss and sleep‐disordered breathing. There is little research on its etiology. Methods: We conducted a case–control study from maternal interview data collected from mothers of infants with and without CFM. The study included 108 children with and 84 children without CFM. Logistic regression with adjustment for demographic factors was used to evaluate associations between maternal exposures of interest and risk for CFM overall, as well as for different phenotypic sub‐groups of children on the CFM spectrum. Results: We found a statistically significant association between diabetes mellitus (DM) and CFM (OR 4.01, 95% CI 1.6–10.5). The association was slightly attenuated after adjustment for BMI. Higher parity was also associated with increased risk for CFM (OR 2.0, 95% CI 1.0–4.0). Vitamin A consumption and/or liver consumption was associated with a 70% lower risk compared with non‐users (OR 0.3, 95% 0.1–0.8). Maternal age at the time of pregnancy was not associated with CFM. Conclusions: These analyses contribute evidence linking maternal DM with an elevated risk of having an infant with CFM, which is consistent with previous research and adds to the body of knowledge about the strength of this association. Further study is warranted to understand the potential mechanisms underlying the effect of DM in the developing embryo.